Evaluation of a thymol formulation efficacy against Varroa destructor under Central Greek climatic conditions - BACANDRITSOS (Ν. ΜΠΑΚΑΝΔΡΙΤΣΟΣ), N.; PAPANASTASIOU (Ι. ΠΑΠΑΝΑΣΤΑΣΙΟΥ), I. (Journal of the Hellenic Veterinary Medical Society, 2017)
The acaricidical formulation based on thymol crystals (main active ingredient) in combination with eucalyptus oil, menthol and camphor crystals was evaluated for its efficacy for two consecutive years (2002 and 2003) the period from 25th May to 25th June. The experimental apiaries are located in Locrida (Central Greece) where the temperatures during summer are usually high. Naturally infected by the mite Varroa destructorbee colonies with similar population were used. The formulation was placed on the upper part of the frames at a rate of one dose every 15 days for two times. The average value of the formulation efficacy was 90.5%±1.0 and 90.6%±0.8 for 2002 and 2003, respectively. In 2002 the temperature in the area where the experiment took place ranged from 17.0°C up to 27.0 °C, while in 2003 it ranged from 16.3°C up to 27.5°C. The results showed that when the bee colonies were treated with two tablets, one every 15 days at the beginning of the summer, the efficacy of the thymol formulation was 90.5% with minimal side effects and toxicity. Additionally, at the beginning of its use, the observed bee agitation at the hive entrance can be reduced by placing 1/20 of the dosage one day before the main treatment.